1993
DOI: 10.1016/s0010-9452(13)80293-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and Associative Knowledge in Category Specific Impairment of Semantic Memory: A Study of two Cases

Abstract: We report two head-injured patients whose knowledge of living things was selectively disrupted. Their semantic knowledge was tested with naming and verbal comprehension tasks and a verbal questionnaire. In all of them there was consistent evidence that knowledge of living things was impaired and that of non-living things was relatively preserved. The living things deficit emerged irrespective of whether the question tapped associative or perceptual knowledge or required visual or non visual information. In all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(50 citation statements)
references
References 17 publications
3
44
1
2
Order By: Relevance
“…4449 Differential impairment for living things has also occurred among head-injury patients and in SD. 50 Furthermore, brain damage can specifically dissociate deficits in animate knowledge compared with inanimate knowledge. 33,51 …”
Section: Discussionmentioning
confidence: 99%
“…4449 Differential impairment for living things has also occurred among head-injury patients and in SD. 50 Furthermore, brain damage can specifically dissociate deficits in animate knowledge compared with inanimate knowledge. 33,51 …”
Section: Discussionmentioning
confidence: 99%
“…The second prediction is that an impairment for a given category of knowledge will be associated with a disproportionate impairment for the modality of knowledge that is critical for that category. At variance with this prediction, it is now known that category-specific semantic deficits are associated with impairments for all types of knowledge (sensory and functional) about items from the impaired category (Figure 2 a ; e.g., Blundo et al 2006, Caramazza & Shelton 1998, Laiacona & Capitani 2001, Laiacona et al 1993, Lambon Ralph et al 1998, Moss et al 1998). The third prediction is that impairments for a type of knowledge will necessarily be associated with differential impairments for the category that depends on that knowledge type.…”
Section: The Neural Structure Principlementioning
confidence: 99%
“…These data show that ( a ) category-specific semantic impairments are associated with impairments for all types of knowledge about the impaired category, ( b ) differential impairments for visual/perceptual knowledge can be associated with (if anything) a disproportionate impairment for nonliving things compared to living things, and ( c ) selective impairment for knowledge of object color is not associated with a corresponding disproportionate deficit for fruit/vegetables. Data for EW from Caramazza & Shelton 1998; GR and FM from Laiacona et al 1993; DB from Lambon Ralph et al 1998; and RC from Moss et al 1998.…”
Section: Figuresmentioning
confidence: 99%
“…With respect to the Sensory-Functional theory, studies have shown that patients with a specific deficit in reasoning about living things are just as impaired in reasoning about animals’ functional features as their sensory features – a finding clearly at odds with the theory (Funnell & De Mornay Davies, 1997; Laiacona, Barbarotto, & Capitani; 1993; Laiacona et al, 1997; Sheridan & Humphreys, 1993). The Organized Unitary Content Hypothesis fares better with respect to the evidence, but this may be, as Caramazza and Shelton (1998) suggest, because it is an inadequately constrained theory to begin with, able to explain virtually any finding.…”
Section: Conservation Of Species Volume and Belief: Studies Of Possmentioning
confidence: 99%